A predictive study on effective thermal conductivity of sintered nickel powder under different thermal processing conditions. (April 2022) - Zhang, Yuankun; Han, Zhuosheng; Wu, Shouyu; Rhamdhani, Akbar; Guo, Chunsheng; Brooks, Geoffrey
Highlights: A predictive model for effective thermal conductivity of sintered nickel sample. The model is based on the circuit equivalent model and neck formation theory. 48 nickel porous samples are fabricated by orthogonal design under high vacuum. A dimensionless factor was proposed with its physical meaning verified. Model with different particle sizes is presented and experimentally validated. Abstract: Effective Thermal Conductivity (ETC) plays a key role in the thermal performance evaluation of samples with porous structure, which can be characterized by multiple physical properties such as particle sizes, porosity, and surface energy. The thermal conductivity of un-sintered porous material has been highlighted in most previous studies, while the evaluation of sintered thermal conductance is scarcely mentioned before. This study aims to develop an analytical model for the ETC prediction of sintered nickel powders based on the circuit equivalent model and sintering neck formation theory. Here, sixteen groups of sintering samples in three particle sizes are fabricated according to orthogonal design with four levels and four key factors, including sintering temperature (650∼800 °C), compressional stress (10∼25 MPa), heating rate (7∼20 °C/min), and holding time (1∼3 h). A dimensionless factor, formulated by the ratio of shrinkage rate to sintering contact area fraction, is proposed to reflect the effect of pore combination and grain growth at the late stage of sintering. The presented model is experimentally validated with an average deviation of three particle sizes equal to 7.11%, 6.38%, and 3.48%, respectively. Besides, simulated ETC agrees well with measured data for samples with medium-high porosity (0.44∼0.71) compared to those prepared with pore-forming agents.